Emotional Intelligence And Work Life Balance In An Organizational Citizenship Behavior (OCB) Perspective With Job Satisfaction As A Mediating Variable (Study on PNS at BPS Makassar City) - Nur Padilah (Scientia Integritas Utama, 2022)
This study aims to analyze emotional intelligence and work-life balance from the perspective of organizational citizenship behavior with job satisfaction as a mediating variable in civil servants at BPS Makassar City. The population in this study was 35 civil servants (PNS) at BPS Makassar city. The sampling method is a saturated sample, so the entire population is used. Data collection was carried out through interviews and distributing questionnaires through Google Forms. The data analysis used is the validity and reliability test of the classical assumption test, path analysis, hypothesis testing, and Sobel test. The analysis results show that emotional intelligence positively and significantly affects job satisfaction. Work-life balance has no direct effect on job satisfaction. Job satisfaction has a positive and significant effect on organizational citizenship behavior. Emotional intelligence has a direct effect on OCB. Work-life balance has no direct effect on OCB. This study also proved that emotional intelligence affects OCB, which is mediated by job satisfaction. Furthermore, job satisfaction does not mediate the effect of work-life balance on OCB.